2021
DOI: 10.3390/ijms22115779
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated and Improved Vascular Maturity after Transplantation of Testicular Tissue in Hydrogels Supplemented with VEGF- and PDGF-Loaded Nanoparticles

Abstract: Avascular transplantation of frozen–thawed testicular tissue fragments represents a potential future technique for fertility restoration in boys with cancer. A significant loss of spermatogonia was observed in xeno-transplants of human tissue most likely due to the hypoxic period before revascularization. To reduce the effect of hypoxia–reoxygenation injuries, several options have already been explored, like encapsulation in alginate hydrogel and supplementation with nanoparticles delivering a necrosis inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 64 publications
(88 reference statements)
0
14
0
Order By: Relevance
“…Moreover, VEGF can inhibit testicular cell apoptosis [52]. Del Vento and his collaborators [53] have recently shown that VEGF increased testicular vascular maturity both structurally and functionally. We reported a significant decrease in testicular VEGF in the Ec group even after E-cigs cessation in W group.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, VEGF can inhibit testicular cell apoptosis [52]. Del Vento and his collaborators [53] have recently shown that VEGF increased testicular vascular maturity both structurally and functionally. We reported a significant decrease in testicular VEGF in the Ec group even after E-cigs cessation in W group.…”
Section: Discussionmentioning
confidence: 99%
“…Bovine testicular tissue treated with vascular endothelial growth factor (VEGF) at the time of implantation in mice ( 121 ) was heavier at recovery than the untreated control and showed a higher percentage of seminiferous tubules containing differentiated cells. Since the early approaches, numerous experiments have begun to treat the tissue with VEGF, whether in the context of autografts in mice ( 122 ), bovine tissue xenografts ( 123 ), and even pre-pubescent human testis xenografts ( 124 ).…”
Section: Fertility Restoration Employing Testicular Tissuementioning
confidence: 99%
“…On the pre-pubescent human testis, in vitro pretreatment with VEGF appears to increase vascularization and survival of SSCs and seminiferous tubule integrity ( 124 ). Subsequent experiments ( 122 ) on autograft in mice tested the combined effect of VEGF and platelet-derived growth (PDGF) nanoparticles, showing that the combination of the two factors appears to further improve vascularization. The use of necrosis inhibitor substances also seems promising ( 125 ).…”
Section: Fertility Restoration Employing Testicular Tissuementioning
confidence: 99%
“…VEGF is synthesized from Sertoli and Leydig cells in the male genital tract, as well as from peritubular cells of the epididymis, prostate epithelial cells, and seminal vesicle. VEGF is very important in germ cell homeostasis and may regulate male fertility in testes [ 29 , 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%